Comparison of Corticosteroid Tapering Regimens in Myasthenia Gravis - Tarek Sharshar; Raphaël Porcher; Sophie Demeret; Christine Tranchant; Antoine Guéguen; B. Eymard; Aleksandra Nadaj‐Pakleza; Marco Spinazzi; Lamiae Grimaldi; Simone Birnbaum; Diane Friedman; Bernard Clair; et al. (2021)
The tapering of prednisone therapy in generalized myasthenia gravis (MG) presents a therapeutic dilemma; however, the recommended regimen has not yet been validated.To compare the efficacy of the standard slow-tapering regimen of prednisone therapy with a rapid-tapering regimen.From June 1, 2009, to July 31, 2013, a multicenter, parallel, single-blind randomized trial was conducted to compare 2 regimens of prednisone tapering. Data analysis was conducted from February 18, 2019, to January 23, 2020. A total of 2291 adults with a confirmed diagnosis of moderate to severe generalized MG at 7 specialized centers in France were assessed for eligibility.The slow-tapering arm included a gradual increase of the prednisone dose to 1.5 mg/kg every other day and a slow decrease once minimal manifestation status of MG was attained. The rapid-tapering arm consisted of immediate high-dose daily administration of prednisone, 0.75 mg/kg, followed by an earlier and rapid decrease once improved MG status was attained. Azathioprine, up to a maximum dose of 3 mg/kg/d, was prescribed for all participants.The primary outcome was attainment of minimal manifestation status of MG without prednisone at 12 months and without clinical relapse at 15 months. Intention-to-treat analysis was conducted.Of the 2291 patients assessed, 2086 did not fulfill the inclusion criteria, 87 declined to participate, and 1 patient registered after trial closure. A total of 117 patients (58 in the slow-tapering arm and 59 in the rapid-tapering arm) were selected for inclusion by MG specialists and were randomized. The population included 62 men (53%); median age was 65 years (interquartile range, 35-69 years). The proportion of patients having met the primary outcome was higher in the rapid- vs slow-tapering arm (23 [39%] vs 5 [9%]), with a risk ratio of 3.61 (95% CI, 1.64-7.97; P < .001) after adjusting for center and thymectomy. The rapid-tapering regimen allowed sparing of a mean of 1898 mg (95% CI, -3121 to -461 mg) of prednisone over 1 year (ie, 5.3 mg/d per patient, P = .03). The number of serious adverse events did not differ significantly between the slow- vs rapid-tapering group (13 [22%] vs 21 [36%], P = .15).In patients with moderate to severe generalized MG who require high-dose prednisone with azathioprine therapy, rapid tapering of prednisone appears to be feasible, well tolerated, and associated with a good outcome.ClinicalTrials.gov Identifier: NCT00987116.